International Centre for Reindeer Husbandry (ICR) (2009)
The International Centre for Reindeer Husbandry (ICR) was established by the Norwegian Government in 2005 in Kautokeino, as a contribution to the unique international cooperation of circumpolar reindeer herding peoples. ICR is an independent professional unit, with its own board and budget. ICR is to be a knowledge base for providing and exchanging information and documentation between different reindeer peoples, national authorities and research- and academic communities at the national and international levels.